Memorizing the Quran with hypnotherapy method - Syahdiah, Utami; Budiman, Budiman; Nur Kholifah, Umi (INSPIRA: Indonesian Journal of Psychological Research, 2023)
Memory productivity in the brain can work in Quran memorization activities through hypnotherapy. It can increase the function of neurotransmitters and manage the hippocampus, which works in memory storage. This study aims to examine hypnotherapy as one of the methods of memorizing the Qur'an. The research subjects were selected through the hypnotherapy stage, where a suggestibility test was conducted. The total number of students in Rumah Tahfidz Al-Muhajirin is 22 students. In the results of the suggestibility test, there are nine children with high trance conditions and 13 students with lower trance conditions. The research subjects were nine students with high trance states. The research subjects are female students with an age range from 9 to 13 years. This research is quantitative with an experimental method and a one-group pretest-posttest research design. The data source was obtained directly from the research subject, using data collection through the interview method and data collection tools in the form of Al-Qur'an memorization intensity instruments. Data analysis uses percentage techniques based on the Wilcoxon signed ranks test method with descriptive analysis results. The results of this study based on the pre-test score of 72% and the post-test score of 90% showed an increase of 18%. This research offers an influence in improving the memorization of Al-Quran with the hypnotherapy method. This result implies that hypnotherapy is not only a technique that can be used in healing or therapy but can also improve the memorization of the Quran.